Effect of Cow Manure and Atonic on Spinach (Amaranthus spp.) Production in Dry Land - Uly J Riwu Kaho; Joritha Naisanu; Karolina Satria Ida (Jurnal Biologi Tropis, 2020)
East Nusa Tenggara is dominated by dry land which has the potential for the development of horticultural crops. Horticultural plants that are widely cultivated by the community are spinach. However, in reality, spinach production in this province is still fluctuating, this is due to the low knowledge of farmers about providing proper nutrition for plant growth and development. For this reason, this study aims to determine the production of spinach in dry land due to cow manure and atonic application. This research was conducted in the experimental field of the Faculty of Agriculture, University of the Teachers Association 1945. The design used was a factorial randomized block design (RBD), which consisted of 2 factors: factor I: cow manure and factor II: growth stimulant (atonic). The results obtained were: The application of cow manure and atonic manure to spinach on dry land had a very significant effect on plant height (7,55 -F hitung> 4,77-F Tabel), number of leaves (10.85-F hitung> 4,77-F Tabel), fresh weight (13,98-F hitung) > 4,77-F Tabel) and dry weight (6,44 -F hitung) > 4,77 -F Tabel).